Evaluación de clima organizacional y nivel de desarrollo de la creatividad en los colaboradores del centro de desarrollo comunitario Versalles del municipio de Manizales, departamento de Caldas, Colombia. (2020)
The objective of this research is to carry out Organizational Climate Assessment and level of creativity development in the collaborators of the Centro de Desarrollo Comunitario Versalles of the Municipality of Manizales, Department of Caldas, Colombia. Through descriptive research and experimental design. The evaluation of the information will be made using the modified Organizational Climate Test (TECLA); with the incorporation of 45 items to know the level of development of Creativity in the Collaborators. However, it is worth mentioning that the research field work will not be carried out, since, at present, there is a public health emergency of international importance due to the coronavirus or commonly called COVID-19, affecting the application of the instrument of the present study. However, an exhaustive description of the entire field procedure from start to finish is chosen and proceeds in order to provide the necessary elements and be able to apply the instrument at a later time.